Contesting human remains in museum collections : the crisis of cultural authority - Jenkins, Tiffany (New York : Routledge, 2011)
An examination of the construction of contestation over human remains from a sociological perspective, this work advances an emerging area of academic research, setting the terms of debate, synthesizing disparate ideas, & making sense of a broader cultural focus on dead bodies in the contemporary period.
An examination of the construction of contestation over human remains from a sociological perspective, this work advances an emerging area of academic research, setting the terms of debate, synthesizing disparate ideas, & making sense of a broader cultural focus on dead bodies in the contemporary period.
Transforming concerns about human remains into an issue -- Scientists contest repatriation -- The crisis of cultural authority -- The rise and impact of pagan claims-makers -- Explaining why human remains are a problem -- Covering up the mummies -- Concluding thoughts.
"Simultaneously published in the UK"--T.p. verso.
Includes bibliographical references (p. [147]-165) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Cultural property -- Repatriation; Cultural property -- Moral and ethical aspects; Cultural property -- Political aspects; Indigenous peoples -- Antiquities -- Collection and preservation; Museums -- Collection management -- Moral and ethical aspects; Museums -- Collection management -- Political aspects; Human remains (Archaeology) -- Repatriation; Human remains (Archaeology); Electronic books